2016
DOI: 10.1111/ppa.12524
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of elm yellows phytoplasmas in Croatia and their impact on Ulmus spp.

Abstract: Candidatus (Ca.) Phytoplasma ulmi', the causal agent of elm yellows, was found widely distributed across elm populations in Croatia, infecting Ulmus laevis and Ulmus minor. Especially high prevalence of the infection, approximately 75%, was detected in U. laevis, but more than half of the trees were symptomless. 'Candidatus Phytoplasma solani' and 'Ca. Phytoplasma asteris' were also detected. The latter could possibly represent a new 16SrI subgroup, most closely related to 16SrI-B. Diversity of 'Ca. Phytoplasm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(36 citation statements)
references
References 27 publications
(83 reference statements)
1
32
3
Order By: Relevance
“…Bacterial elm yellows has been found on U. glabra in Croatia, France and Germany belonging to Candidatus Phytoplasma solani (16SrXII-A subgroup) (Boudon-Padieu et al, 2004;Katanić, Krstin, Ježić, Zebec, & Ćurković-Perica, 2016;Mäurer, Seemüller, & Sinclair, 1993), and hybrids of U. glabra in North America (Sinclair, Townsend, Griffiths, & Whitlow, 2000). It causes witches brooms and yellowing of leaves (Mittempergher, 2000).…”
Section: Bacteriamentioning
confidence: 99%
“…Bacterial elm yellows has been found on U. glabra in Croatia, France and Germany belonging to Candidatus Phytoplasma solani (16SrXII-A subgroup) (Boudon-Padieu et al, 2004;Katanić, Krstin, Ježić, Zebec, & Ćurković-Perica, 2016;Mäurer, Seemüller, & Sinclair, 1993), and hybrids of U. glabra in North America (Sinclair, Townsend, Griffiths, & Whitlow, 2000). It causes witches brooms and yellowing of leaves (Mittempergher, 2000).…”
Section: Bacteriamentioning
confidence: 99%
“…In Friuli Venezia Giulia, widespread occurrence of EY on Siberian elm has also been observed (Carraro et al, 2004). However, more than half of the infected trees were symptomless (Katanić et al, 2016). However, more than half of the infected trees were symptomless (Katanić et al, 2016).…”
Section: European Field Elm Have Been Observed In the Po Valley And Fmentioning
confidence: 88%
“…P. ziziphi" (the jujube witches' broom agent) by less than 2.5% in 16S rDNA sequence similarity, the threshold for assigning species rank to phytoplasmas under the provisional status "Candidatus" (IRPCM Phytoplasma/Spiroplasma Working Team -Phytoplasma taxonomy group, 2004). P. ulmi" strains infecting elm trees in Serbia and Croatia (Jović et al, 2011;Katanić et al, 2016), which differ from the "Ca. Nucleotide sequence comparisons revealed that four strains of "Ca.…”
Section: Taxonomic Positionmentioning
confidence: 98%
See 2 more Smart Citations